Tindak Tutur Ilokusi tentang Penyalahgunaan Agama di Kanal Youtube Raymond Chin - Rani Febriolla De Lima; Maulani Apriliani; Mahkota Teja Kusuma; Natalia Kartika Saputri; Muhammad Isky Yanuar Najib; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Dwiana Asih Wiranti (Simpati, 2026)
This study aims to examine illocutionary speech acts used in the context of religious abuse. This problem is examined in pragmatics, specifically through illocutionary speech acts. This study aims to identify and describe the types of illocutionary speech acts in the context of religious abuse in digital media. This study uses a qualitative descriptive approach with a pragmatic theoretical approach. Data were obtained through the listening-and-note-taking method from the video series "#ESCAPE - Raymond Chin X Ustadz Felix Siauw," which focuses on religious abuse, and then analyzed using the matching method. The results of the study indicate the presence of illocutionary speech acts, namely assertive, directive, expressive, commissive, and declarative used to convey certain intentions. These speech acts not only function as linguistic and educational tools, but also encourage critical thinking among the audience and have the potential to shape opinions. The dominant illocutionary speech act in the video is the assertive type. This is because the speaker mostly delivers statements, explanations, and arguments to provide information. This study contributes to the development of pragmatic research and increases public critical awareness of sensitive issues.